A blue carbon pilot project: Lessons learned. Issue 1 (2nd January 2022) - Mack, Sarah K.; Lane, Robert R.; Holland, Kyle; Bauer, Julian; Cole, Jeff; Cowan, Rori
Abstract: Here we describe a pilot wetland carbon project located 30 km west of New Orleans where measurements were taken in 2013 and 2018, and applied to a carbon offset methodology published by the American Carbon Registry (ACR). Baseline emissions were modeled using values derived from scientific literature, which resulted in a net sequestration rate of 16, 527 t CO2-e (tons carbon dioxide equivalents) per year if wetland greenhouse gases (CH4 & N2 O) were included (619, 727 over the 40-year project duration), and 5, 003 t CO2-e/yr if wetland greenhouse gases were conservatively omitted (200, 143 t CO2 e over 40 years). Alternatively, a kriging exercise was carried out that modeled the tree and soil pools, resulting in higher net sequestration of 18, 084 t CO2-e/yr with greenhouse gases (723, 375 t CO2-e over 40 years), and 6, 560 t CO2-e/yr if greenhouse gases were omitted (262, 472 t CO2-e over 40 years). Unfortunately, the project was withdrawn, prohibiting the issuance and eventual transaction of carbon credits, due to very large uncertainty estimates mostly associated with methane and nitrous oxide emissions as well as the kriging approach since in situ sampling could not be carried out as required by the methodology. Next steps to increase the commercial viability of wetland carbon offsets include: closing knowledge gaps in wetland emissions of methane and nitrous oxide; developing means to reduce costs of monitoring, reporting and verification; fully accounting for prevented loss; developing remote sensing methods for monitoring and verification; and development of biogeochemical models to predict methane and nitrous oxide fluxes and sequestration pools. Though the project did not generate carbon credits, the results and lessons learned are intended to inform managers, and blue carbon project developers on how to develop wetland carbon credits that are high quality, economically competitive, and scientifically defensible.